Effects of Islamic Spiritual Mindfulness on Stress among Nursing Students - Munif, Badrul; Poeranto, Sri; Utami, Yulian Wiji (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Academic stress is a major problem that often occurs in nursing students. Islamic spiritual mindfulness (ISM) is an adaptive coping strategy used to mitigate various negative psychological reactions to respond stressors experienced by the body to build self-awareness that any problems experienced today are the scenario of Allah.Purpose: This study aimed to determine the effects of Islamic spiritual mindfulness therapy to reduce stress.Methods: This study used a pre-post quasi-experimental design with a control group. Participants were bachelor students of nursing who are Muslim and experienced stress in working on the thesis (n=36) and were assigned to two groups: the experimental group receiving Islamic spiritual mindfulness and the control group. Data were collected using questionnaires of Depression Anxiety Stress Scale (DASS) and analyzed using paired t-test and unpaired t-test. Results: The results showed that the mean stress level of students in the intervention group decreased from 20.6±2.97 to 11.4±5.81 after the intervention. Meanwhile, in the control group, the mean student stress level slightly decreased from 19.7±2.82 to 17.8±5.01. The t-test obtained a p-value of 0.001, indicating that there were significant differences in stress levels between the intervention group and the control group. The effect size obtained the value of 0.59, meaning the level of influence was in the medium category.Conclusion: This study concluded that Islamic spiritual mindfulness was effective in reducing stress among nursing students working on the thesis. It is recommended for the nursing profession, especially mental health nurses, to apply Islamic spiritual mindfulness therapy as one of the psychotherapy interventions.